Determining the influence of different levels of urea supplementation when beef cows grazing winter pasture are supplemented at different frequencies during the prepartum period - Farmer, C.G.; Cochran, R.C.; Wickersham, T.A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred sixty spring-calving Hereford × Angus cows grazing low-quality, tallgrass-prairie range during the winter of 2000-2001 were supplemented before calving either daily or three times weekly. The supplement contained 40% CP with 0, 15, 30, or 45% of the supplemental degradable intake protein from urea. Supplement was fed at 4 lbs/head daily to cows receiving supplement daily. Cows receiving supplement three times weekly were fed the same amount of weekly supplement, but split equally among their supplementation events. After calving, all cows received a supplement without urea on a daily basis. In general, prepartum supplements that contained more urea prompted greater body weight loss; however, the effect of increasing urea was most noticeable when supplements were fed only three times weekly. When averaged across supplementation frequencies, increasing the level of supplemental urea tended (P=0.15) to decrease pregnancy rate in beef cows that had received urea supplementation before calving.
Keywords: Beef; Range; Supplementation; Frequency; Urea